PENGARUH MODEL PEMBELAJARAN PROJECT-BASED LEARNING BERBASIS MEDIA PADLET TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA SMK - Zunia Faradinna Ikrima; Lifa Farida Panduwinata (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Creative thinking skills are essential competencies in 21st-century education and the workplace because they play a key role in problem solving and innovation. The Project-Based Learning (PjBL) model, when combined with digital tools such as Padlet, has the potential to enhance students’ creativity through real-world experiences and collaboration. This study aims to examine the effect of implementing PjBL combined with Padlet on students’ creative thinking skills in the Creative Projects and Entrepreneurship course at SMK Negeri 2 Kota Kediri. This study employs a quantitative approach using a quasi-experimental design conducted on a control class and an experimental class, comprising a total of 71 11th-grade MPK students. Data collection was conducted using a learning implementation checklist and a creative thinking ability test using elements of the Business Model Canvas (BMC) that had been validated for validity, reliability and reviewed by experts, the data were then analyzed using the N-Gain Score and the Mann-Whitney Test. The results indicate that the implementation of the Padlet-based PjBL model was categorized as “very good,” meaning that all learning components were implemented as planned. Furthermore, the analysis results indicate that instruction using the Padlet-based PjBL model has a significant effect on students’ creative thinking skills. This demonstrates that the application of the Project-Based Learning model combined with Padlet is effective in enhancing students’ creative thinking skills through a learning process that encourages collaboration, exploration of ideas, and active project completion, thereby serving as an innovative alternative instructional model that supports the development of 21st-century competencies.